Quality of life 3 and 12 months after acute pulmonary embolism: analysis of 617 patients from the prospective multicentre FOCUS study. (25th November 2020) - Valerio, L; Barco, S; Jankowski, M; Rosenkranz, S; Lankeit, M; Held, M; Gerhardt, F; Bruch, L; Ewert, R; Faehling, M; Freise, J; Ardeschir Ghofrani, H; et al.
Abstract: Background: Few data are available on the long-term course and predictors of quality of life (QoL) after acute pulmonary embolism (PE). Aims: To evaluate the kinetics and determinants of QoL at 3 and 12 months after acute PE. Methods: The Follow-Up after acute pulmonary embolism (FOCUS) study prospectively followed consecutive adult patients with objectively diagnosed PE. For this analysis, we considered patients who completed the Pulmonary Embolism QoL (PEmb-QoL) Questionnaire at two predefined visits 3 and 12 months after PE. PEmb-QoL, studied as total score and in its six dimensions, ranges from 0% (best QoL) to 100% (worst QoL). We studied the course of PEmb-QoL and the impact of baseline characteristics using multivariable linear regression. Results: In 617 included patients (44% women, median age 62 years), overall QoL improved from 3 to 12 months, with a decrease of the mean PEmb-QoL score from 25.3% to 21.5% (p-value <0.001). Intra-individual correlation between PEmb-QoL score at 3 and 12 months was high; Figure A. The improvement was consistent across all PEmb-QoL dimensions; Figure B. Female sex, cardiopulmonary diseases, and higher body mass index were the main factors associated with a worse QoL; Table. Age and smoking affected QoL only at 12 months. The improvement in QoL was faster in patients without cardiopulmonary diseases (−4.2%; 95% CI: −5.2% to −3.1%), without previous VTE (−4.3%; −5.5% to −3.2%), and in non-smokers (−4.2%; −5.3% to −3.1%). Conclusions: In a large cohort of patients with pulmonary embolism, we quantified the improvement of QoL between 3 and 12 months after diagnosis. We identified factors independently associated with lower QoL and slower recovery of QoL that may reflect special patient needs. These estimates may facilitate the planning and interpretation of clinical trials with QoL as a study outcome. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): University Medical Center of the Johannes Gutenberg University, Mainz, Germany; German Federal Ministry of Education and Research